Physical chemistry with applications to Biological Systems - Chang, Raymond (Macmillan Publishing, 1977)
The gas laws.--Kinetic theory of gases.--The soil state.--Quantum mechanics.--Atoms and molecules.--Intermolecular forces.--Spectroscopy.--Molecular symmetry and optical activity.--Statiscal mechanics.--Thermodynamics.--Nonelectrolyte solutions.--Electrolyte solutions.--Electrochemistry.--Acids and bases.--Chemical kinetics.--Photochemistry and photobiology.--Macromolecules.--Nuclear chemistry.